(untitled) (Eurasian Journal of History, Geography and Economics, 2025)
Today in Uzbekistan there are some issues in the practical application of IFRS. To find a solution to these problems, in this article we want to reveal the essence of IFRS 5 “Noncurrent assets held for sale and discontinued operations” and give some explanations of the organization of accounting for non-current assets held for sale according to international accounting standards and the preparation of financial statements, showing their practical application using the specific examples.